An Evaluation of a Working Memory Training Scheme in Older Adults - McAvinue, Laura P.; Golemme, Mara; Castorina, Marco; Tatti, Elisa; Pigni, Francesca M.; Salomone, Simona; Brennan, Sabina; Robertson, Ian H. (Frontiers in Aging Neuroscience, 2013)
Working memory is a cognitive process that is particularly vulnerable to decline with age. The current study sought to evaluate the efficacy of a working memory training scheme in improving memory in a group of older adults. A 5-week online training scheme was designed to provide training in the main components of Baddeley’s (2000) working memory model, namely auditory and visuospatial short-term and working memory. A group of older adults aged between 64 and 79 were randomly assigned to a trainee (n = 19) or control (n = 17) group, with trainees engaging in the adaptive training scheme and controls engaging in a non-adaptive version of the programme. Before and after training and at 3- and 6-month follow-up sessions, trainees and controls were asked to complete measures of short-term and working memory, long-term episodic memory, subjective ratings of memory and attention and achievement of goals set at the beginning of training. The results provided evidence of an expansion of auditory short-term memory span, which was maintained 6 months later, and transfer to long-term episodic memory but no evidence of improvement in working memory capacity per se. A serendipitous and intriguing finding of a relationship between time spent training, psychological stress and training gains provided further insight into individual differences in training gains in older adults.